Yield and economic returns of peanut and sweetcorn as influenced by timing of planting the crops in an intercropping scheme - Cagasan, Ulysses A.; Agarcio, Benjamin (Annals of Tropical Research, 2004)
This study was conducted to evaluate the growth and yield of peanut and sweet corn as influenced by timing of planting the crops in an intercropping scheme; determine the appropriate timing of planting peanut and sweet corn in an intercropping scheme for optimum land productivity; and determine the economics of growing peanut in combination with sweet corn as influenced by timing of planting the crops. Most of the agronomic characteristics, yield and yield components of peanut and sweet corn were significantly affected by timing of planting the crops. Sweet corn planted 2 and 3 weeks ahead of peanut gave higher total yield in tons per hectare than sweet corn planted later than peanut. Planting sweet corn 3 weeks ahead of peanut (T3) gave the highest land equivalent ratio (LER) of 1.62, which means that such practice was 62% more productive than growing peanut or sweet corn as monocrop. It also gave the highest gross margin of PhP 52,157.00 per hectare.